2014
DOI: 10.1186/1472-6947-14-60
|View full text |Cite
|
Sign up to set email alerts
|

User-centered design of a web-based self-management site for individuals with type 2 diabetes – providing a sense of control and community

Abstract: BackgroundTo design and test a web-based self-management tool for patients with type 2 diabetes for its usability and feasibility.MethodsAn evidence-based, theory-driven website was created for patients with type 2 diabetes. Twenty-three patients with type 2 diabetes aged ≥ 25 years were recruited from 2 diabetes care centers in Toronto, Canada. We employed focus group methodology to assess acceptability, sustainability, strengths and weaknesses of the self-management website. Based on these results, revisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 37 publications
(43 reference statements)
0
69
0
1
Order By: Relevance
“…In a previous study, we developed an approach to address many of these limitations of existing web-based interventions [ 15 ]. In the current study, we tested the impact of this approach on self-efficacy, quality of life, self-care, blood pressure, cholesterol, glycemic control, and exercise promotion amongst people with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we developed an approach to address many of these limitations of existing web-based interventions [ 15 ]. In the current study, we tested the impact of this approach on self-efficacy, quality of life, self-care, blood pressure, cholesterol, glycemic control, and exercise promotion amongst people with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The proper sample size is essential for usability testing, so that research, which found that up to 80% of usability has issues, can be determined with 5 to 8 participants [51]. Based on our usability testing, Jakob Nielsen's general principles for interaction design such as error prevention, consistency and standards, aesthetic and minimalist design, recognition rather than recall, and help and documentation are required to be considered, and which were addressed on our app through iterative refinement process [52]. One of the most important cases in intervention implementation is usability testing [53] but this is often neglected, with up to 60% of diabetes-related websites having a minimum of 4 usability errors.…”
Section: Discussionmentioning
confidence: 99%
“…Improving access to health information does not just involve citations and references, but the information need to be filtered and synthesized. Information overload from the website potentially could distract people from the website and therefore reduce the website usage [44]. Information on the websites should not only be personalized to health background, but also personalization should be made according to user`s location, culture and language [45].…”
Section: Patient-tailored Informationmentioning
confidence: 99%
“…Information on the websites should not only be personalized to health background, but also personalization should be made according to user`s location, culture and language [45]. User should be able to see the overview of the website content, and then select more detail information personalized to their individual needs [29], [44]. Personalized websites were evident to increase patients` satisfaction, improve understanding of disease and increase ability to involve in managing diseases [46].…”
Section: Patient-tailored Informationmentioning
confidence: 99%